2020
DOI: 10.1159/000507362
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Adenoma as a Rare Cause of Persistent Hypercalcemia in a Female with Polycythemia Vera

Abstract: Polycythemia vera is one of the myeloproliferative neoplasms that is distinguished by the uncontrolled production of blood cells and an increased red cell mass due to acquired JAK2 mutation. It has many complications and it might increase the risk of other tumors. However, it does not cause hypercalcemia and is rarely associated with parathyroid adenoma. Here, we report on a 64-year-old female with polycythemia vera found to have hypercalcemia due to parathyroid adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Absolute polycythemia has two kinds: primary and secondary polycythemia [ 6 ]. Usually, secondary polycythemia results from other conditions that raise the formation of erythropoietin and it is commonly linked with solid tumors [ 2 , 3 ], while the primary polycythemia is developed by bone marrow disorders, which mainly cause abnormal erythroid cell line production [ 7 ]. Furthermore, in rare occasions, PV can be familial when one or various MPN affect diverse kinsfolks of the same family [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Absolute polycythemia has two kinds: primary and secondary polycythemia [ 6 ]. Usually, secondary polycythemia results from other conditions that raise the formation of erythropoietin and it is commonly linked with solid tumors [ 2 , 3 ], while the primary polycythemia is developed by bone marrow disorders, which mainly cause abnormal erythroid cell line production [ 7 ]. Furthermore, in rare occasions, PV can be familial when one or various MPN affect diverse kinsfolks of the same family [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a reported case by Abdalhadi et al which showed an association of PV with a benign tumor, which was a parathyroid adenoma in a woman diagnosed with PV in 2010 who fulfilled the 2008 WHO criteria [ 2 ]. The patient had hypercalcemia, and a neck ultrasound revealed regular-sized thyroid gland with heterogeneous nodules in the left, and cystic nodule in the right lobe, moreover, in the region of both parathyroid glands two hypoechoic nodes were suspected [ 2 ]. The patient was followed by an endocrinologist, who started her on cinacalcet and referred her to the surgical team for parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations